Social economy: Mapping and Interpreting Alternative Economic Experiences in Ecuador - Tituaña, Sandra; Tulia Ospina, Ana; Cabezas, Martha; Mármol, David (Whispers from below: Community-based tourism and (other) Ecuadorian initiatives for alternative economies: A closer look, 2026)
This analysis examines the solidarity economy in Ecuador as a viable alternative to the capitalist system. The research focuses on the ability of various collective initiatives to generate surpluses that go beyond mere subsistence and ensure broader social reproduction. It highlights the role of self-employment and associationalism in contexts of job insecurity, arguing that community-based resource management can foster more equitable and autonomous economic structures.